SAFETY OF TASTINGS IN ENOGASTRONOMIC TOURISM - Калмыкова, Ирина; Шекера, Светлана (SWorldJournal, 2022)
The activity of tasting rooms as an integral element of wine and food tourism is rapidly developing both throughout the world and in Ukraine. Now tastings have resumed in various enogastronomic locations despite the COVID-19 pandemic, so compliance with s